Pengaruh Penerapan Knowledge Management Terhadap Kinerja Perguruan Tinggi dengan Budaya Organisasi Sebagai Variabel Intervening - Masduki Masduki (Masoem University, 2020)
The knowledge management process will create a new culture, namely knowledge sharing that is strong enough and able to create good organizational performance, however, there are still many organizations or companies that have not implemented knowledge management properly. This study aims to determine whether the application of knowledge management has a significant influence on the performance improvement of Majalengka University with organization culture as an intervening variable. The research method used is a survey method with the type of associative research. The author took a sample of 77 permanent lecturers and DPK Majalengka University. Data were collected through a questionnaire in the form of a statement list, the method of data analysis using Partial Least Square (PLS) with the help of smart-PLS 3.0 software. The results of this study indicate that the application knowledge management and organizational culture contribute directly positively and significantly to improving the performance of Majalengka University, knowledge management contributes positively and significantly to strengthening organizational culture, and organizational culture is able to mediate knowledge management in contributing to improving the performance of Majalengka University.